Pertimbangan Sosiologis Penegakan dan Pengamalan Hukum Islam di Indonesia - Muhammad Taufan Djafri; Kurniati Kurniati; Misbahuddin Misbahuddin (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
This study aims to analyze the sociological considerations of enforcement and application of Islamic law in Indonesia. This research is a library research that is qualitative in nature. The results of the study show that the sociology of Islamic law is a reciprocal relationship between Islamic law (Syarī'ah, Fiqh, al-Ḥukm, Qānūn, etc.) and patterns of societal behavior in which Sociology is one approach in understanding it. In essence, Islamic law in Indonesia is legal norms originating from Islamic law that grew and developed in people's lives throughout the history of Indonesia. Theories of thought regarding the application of Islamic law in Indonesia are formalistic-legalistic thought theory, structuralistic thought theory, culturalistic thinking theory and substanialistic-applicative thinking theory. It turns out that the enforcement and application of Islamic law has many obstacles so that Islamic law seems very slow, especially in the field of jinayat (Islamic crime).